Evaluation of Pasteurization and Sterilization Process on Camel Milk Quality (Global Journal of Science Frontier Research, 2022)
Pasteurization and sterilization processes were applied on camel milk and their effect on its quality were evaluated in this study. Camel milk was subjected to the pasteurization and sterilization process using the USPTO UHT+ S1 pilot plant and was examined for its compositional components before and after conducting of heat treatment. The results indicated non-significant (P>0.05) variations between the fresh and both the pasteurized and sterilized camel milk in the mean values of total solids (TS), solids not fat (SNF), fat, free fatty acids (FAA), lactose, protein, casein, urea, citric acid, pH, density and acidity after immediate application of heat treatment and also during the storage period. However, significant (P≤0.05) differences were found in the pH and the freezing point depression (FPD) of the pasteurized milk and the FFA and the acidity of the sterilized milk compared to the raw milk. Moreover, the physicochemical properties of camel milk products showed stability during two weeks of storage at four degree centigrade for the pasteurized milk and room temperature (37°C) for the sterilized milk. The total bacterial count and coliform were significantly (P≤0.05) reduced in the pasteurized and sterilized camel milk.
Keywords: camel milk; pasteurization; sterilization; bacterial loads; shelf life